Finance and Development, December 1982. (Finance and Development; Finance and Development ;, 1982)
This paper highlights that on September 29, 1982, the International Bank for Reconstruction and Development (World Bank) began to offer discount notes under a short-term borrowing program approved by its Board last July. The Bank anticipates that in fiscal year 1983, it will have outstanding up to USD 1.5 billion in short-term discount notes and that it will borrow about USD 8 billion in the fixed-rate medium to long-term markets. The initial offering of notes is being made in the U.S. domestic markets.